Determination the concentration of insulin-like growth factor-I (IGF-I) in saliva of acromegalic patients, and comparison it with the levels of serum IGF-I. - Zwain, Shiamaa; Alani, Sahar H.; Alsammariae, Abdilkarim Y. (Journal of Baghdad College of Dentistry, 2018)
Acromegaly is ametabolic disorder characterized by an acquired progressive somatic disfigurement, mainly involving the face, extremities and many other organs, that are associated with systemic manifestations, caused by excessive secretion of growth hormone and a resultant persistent elevation of insulin-like growth factor-I concentrations. In more than 90% of cases originates from a monoclonal benign pituitary adenoma. Aim of this study to assess the level of insulin-like growth factor-I (IGF-I) in saliva of acromegalic patients, and to compare it with the basal levels of serum IGF-I. Sixty specimens of serum and saliva collected from two groups of subjects (forty acromegalic patients and twenty healthy persons). The specimens were centrifuged and stored at -20ÂºC then IRMA kits were used for estimating insulin like-growth factor-I. The results show that acromegalic patients had significantly higher salivary insulin like growth factor-I concentrations than healthy subjects (mean 21.26 vs. 20.48ng/mL; p=0.041), serum insulin like growth factor-I concentrations (mean 782.21 vs. 199.87ng/mL; p